Enhancing the mechanical, wear and corrosion behaviour of stir casted aluminium 6061 hybrid composites through the incorporation of boron nitride and aluminium oxide particles. (27th January 2020) - Gopinath, S; Prince, M; Raghav, G R
Abstract: This research paper portrays the enrichment of mechanical, wear and corrosion properties of the Aluminium 6061 matrix composite by incorporating hybrid reinforcements. Aluminium 6061 alloy is stir casted with different proportions of boron nitride (BN), Aluminium oxide (Al2 O3 ) and graphite particles. Tensile test reveals that the tensile strength and ductility for the Al 6061-30 BN -10Al2 O3 - 5C is improved due to the presence of higher BN content along with 10% Al2 O3 . Significant improvement in microhardness (63HV), compressive strength (187 Pa) and impact strength (12 J) for the Al 6061-30 BN -10Al2 O3 - 5C when compared with the bare Al 6061 alloy. The dispersion of BN with Al2 O3 improved the wear resistance for the Al 6061-30 BN -10 Al2 O3 - 5 C composite, where as the unreinforced bare Al alloy has caused the major surface degradation resulting in poor wear property and the worn out surfaces are examined through the scanning electron microscope. The main wear mechanism is identified as adhesive wear. The corrosion test results clearly reveals that the corrosion resistance is higher for the Al 6061-30 BN -10Al2 O3 - 5C (−0.526 ± 0.004 V) with a lower current density of −0.983 ± 0.004 μ A cm −2 than the other composites and bare Al 6061.